Investigation of aerosol effects on the Arctic surface temperature during the diurnal cycle: part 1 – total aerosol effect. (5th April 2017) - Stofferahn, Eric; Boybeyi, Zafer
ABSTRACT: Temperature changes in the Arctic due to anthropogenic climate change are larger in magnitude than those at lower latitudes, with sea ice extent and thickness diminishing since the dawn of the satellite era. Aerosols may play a vital role in determining these changes, as the radiation reaching the Arctic surface is impacted directly by aerosol absorption and scattering, as well as the ability of aerosols to act as cloud condensation nuclei (CCN) and ice nuclei (IN). This study uses the Weather Research and Forecasting Chemistry (WRF‐Chem) model to show the impact of aerosol absorption, scattering, and CCN contribution on the Arctic surface, with a particular focus on how these effects change throughout the diurnal cycle. Part 1 of this two‐part study investigates the changes in surface temperature, radiation, and cloud properties due to the total aerosol effect in the Arctic. A suite of ensemble runs is used to develop a filtering mechanism based upon the t ‐test to eliminate the effects of meteorological variability. While much has been speculated about the cooling role of aerosols, this study shows that aerosols have both a warming and cooling effect. The warming effect is prominent at night, while the cooling effect dominates during the day. In both cases, the magnitude of the effect is dependent upon aerosol concentration.